Mercury Pollution in Minamata - Yokoyama, Hisashi (SpringerBriefs in Environmental Science, 2018)
Methylmercury poisoning; Minamata disease; Methylmercury emission; Methylmercury intoxication; Pollution-related disease; Neurological syndrome; Chemical factory pollution; Chisso Corporation